PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA DESA JATIMULYO MELALUI PENGUATAN USAHA MIKRO BERBASISBIOTEKNOLOGI KONVENSIONAL DI BIDANG PANGAN - Nungky Viana Feranita; Rohim Rohim (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2019)
???????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? (KKN-PPM) Program aims to improve the knowledge, skills and income of the Jatimulyo village female head of household through strengthening conventional biotechnology-based micro enterprises in the food sector. Jatimulyo Village as an agriculture-based village has abundant natural resource potential, one of which is soybeans. By using conventional biotechnology, soybeans can produce a product in the field of food such as tofu, tempeh, and soy milk. The KKN-PPM program is implemented starting from preparation and debriefing, implementation of activities, and preparation of program sustainability plans. Through the KKN-PPM program results were obtained in the form of micro-businesses under the name PEKKA Beringinsalam. The KKN-PPM program received a positive response from the participants, and proved to be able to improve the knowledge, skills and income of the target group.